2022
DOI: 10.33394/jollt.v10i3.5413
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Writing Strategies Used by Students of English Language Department

Abstract: The trend towards more process-oriented academic writing instructions require students to pay more attention to and develop their use of writing strategies to ensure learning success. Accordingly, the current study investigates the use of writing strategies performed by freshmen of the English language department in an Indonesian teaching university. The study is an initial effort to provide a theoretical basis for the development of more student-centered and process-oriented writing instructions for the unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…By necessitating direct engagement in the generation of questions, students not only contribute to the shaping of their learning experiences but also concurrently enhance their comprehension and application of the subject matter (Lating, 2022;Ismiati & Fitria, 2021). The structured involvement in the writing process cultivates a dynamic learning environment where students actively exercise critical thinking skills and develop a nuanced understanding of the intricacies involved in constructing coherent and meaningful observation report texts (Hadi et al, 2021;Dari et al, 2022). Consequently, the Inquiring Mind Want to Know technique emerges as a strategy that not only fosters active participation but also serves as a conduit for elevating students' learning achievements in the realm of writing proficiency.…”
Section: Discussionmentioning
confidence: 99%
“…By necessitating direct engagement in the generation of questions, students not only contribute to the shaping of their learning experiences but also concurrently enhance their comprehension and application of the subject matter (Lating, 2022;Ismiati & Fitria, 2021). The structured involvement in the writing process cultivates a dynamic learning environment where students actively exercise critical thinking skills and develop a nuanced understanding of the intricacies involved in constructing coherent and meaningful observation report texts (Hadi et al, 2021;Dari et al, 2022). Consequently, the Inquiring Mind Want to Know technique emerges as a strategy that not only fosters active participation but also serves as a conduit for elevating students' learning achievements in the realm of writing proficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The root of the problem lies in the intricate nature of writing descriptive text, which necessitates a comprehensive understanding of the schematic structure encompassing orientation, record of events, and reorientation (Erickson, 2022;Hadi & Herlina, 2021). Additionally, students are expected to adeptly incorporate the linguistic features intrinsic to descriptive text, such as specific participants, temporal and spatial circumstances, first-person narration, additive conjunctions, material processes, and past tense utilization (Ariati, 2018;Dari et al, 2022). Failure to assimilate these structural and linguistic elements significantly impedes the students' writing endeavors.…”
Section: Discussionmentioning
confidence: 99%
“…This distinction can be attributed to the fact that the four fundamental language skills -reading, writing, speaking, and listening -are requisites that extend their influence, to varying degrees, across virtually every other subject within the curriculum of educational institutions (Al-zumor, 2021;Astiantih & Akfan, 2023). This ubiquity underscores the pivotal role that English plays in facilitating effective communication and comprehension, which, in turn, are essential for the acquisition of knowledge in diverse academic disciplines (Dari et al, 2022;Dwigustini et al, 2021). Indonesia, as a case in point, places substantial emphasis on the importance of English in its educational framework.…”
Section: Introductionmentioning
confidence: 99%
“…However, the result showed that some students were still not easy to organize their ideas in their mind into their writing. This second challenge is the idea or paragraph organization became challenge for students and lecturer in writing (Astiantih & Akfan, 2023;Dari et al, 2022;Fadli et al, 2022). They did not know how to organize idea into paragraph, theme in discourse, topic and supporting ideas in writing.…”
Section: The Challenges Faced By Thesis Supervisor Lecturers In Guidi...mentioning
confidence: 99%